1994
DOI: 10.1016/s0006-3495(94)80637-x
|View full text |Cite
|
Sign up to set email alerts
|

Protein and acidosis alter calcium-binding and fluorescence spectra of the calcium indicator indo-1

Abstract: The fluorescent indicator indo-1 is widely used to monitor intracellular calcium concentration. However, quantitation is limited by uncertain effects of the intracellular environment on indicator properties. The goal of this study was to determine the effects of protein and acidosis on the fluorescence spectra and calcium dissociation constant (Kd) of indo-1. With 350 nm excitation light, the ratio of indo-1 fluorescence in the absence versus the presence of saturating Ca2+ at wavelength lambda (S lambda) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 20 publications
2
44
2
Order By: Relevance
“…)They found that Rma~/R~in (a parameter similar to our R1/Ro) is several fold smaller in the mouse fibers than in salt solutions, but they also found that the indicator Ko in the fiber was verysimilar to that in the cell-free solutions. The latter finding appears to contradict the results from other laboratories, which have reported a substantial increase in the Ko of indo-1 by interaction with intracellular proteins (Hove-Madsen and Bers, 1992;Baker et al, 1994).…”
Section: Comparison Of the Kd Values Estimated With The Permeabilizatcontrasting
confidence: 85%
See 2 more Smart Citations
“…)They found that Rma~/R~in (a parameter similar to our R1/Ro) is several fold smaller in the mouse fibers than in salt solutions, but they also found that the indicator Ko in the fiber was verysimilar to that in the cell-free solutions. The latter finding appears to contradict the results from other laboratories, which have reported a substantial increase in the Ko of indo-1 by interaction with intracellular proteins (Hove-Madsen and Bers, 1992;Baker et al, 1994).…”
Section: Comparison Of the Kd Values Estimated With The Permeabilizatcontrasting
confidence: 85%
“…A number of studies on many Ca 2+ indicators have shown that the indicator properties are likely to be altered in the cytoplasm, probably by binding to cellular macromolecules: fura-2 (Konishi et al, 1988;Uto, Arai, andOgawa, 1991), indo-1 (Hove-Madsen andBers, 1992;Westerblad and Allen, 1993;Baker et al, 1994), fluo-3 , fura red , and aequorin (Blatter and Blinks, 1991). The present results suggest that fura-2 conjugated to dextran can still bind to cellular proteins.…”
Section: Novel Calibration Methods Of the Intracellular Indicator Withmentioning
confidence: 54%
See 1 more Smart Citation
“…In addition, intracellular environments also affect spectral properties of some Ca 2ϩ indicators. It has been demonstrated that indo 1 and fura 2 exhibit different emission/ absorption spectra in intracellular environments compared with buffers (19,161,288). The discrepancy may be caused in part by the absorption/scattering by intracellular constituents (288) and changes in the polarity (288,289) and/or the viscosity (111, 362) of the environment.…”
Section: B In Vivo Calibrationmentioning
confidence: 99%
“…The 10% value was chosen based on earlier reports of the Indo-1 ratio in cells and the relative intensity changes measured by other fluorescent Ca 2+ indicators in migrating fish keratinocytes (Baker et al, 1994;Lee et al, 1999;Doyle et al, 2004;Huang et al, 2009). This value provided an objective criterion for analysis and enabled good separation between the background variation of the lamellipodial intensity and the Ca 2+ sparks.…”
Section: Image Processingmentioning
confidence: 99%